Estrutura genética das populações de abelhas africanizadas (Apis mellifera L.) e suas relações com as raças parentais determinadas por meio da análise de microssatélites - Collet, Thaís (Universidade Federal de São Carlos, 2009)
The Africanization process through the Americas started in 1956 with the introduction in Rio Claro (SP) of Apis mellifera scutellata queens from South Africa. The resultant alterations of this process in the characteristics of the preexisting honeybee populations have been measured through several methods, including morphometry, allozymes, mitochondrial DNA patterns and in a lower degree the microsatellite loci. The aim of this study was to determine the genetic structure of the A. mellifera Africanized populations from seven countries of South and Central Americas, employing 12 microsatellite loci. Parental populations from Europe and Africa were used as control. The results obtained from 2034 colonies analyzed indicated that the American Africanized populations presented a high variability and have essentially an African genetic constitution. The South region of Argentina is an exception since those samples keep the variation patterns of the European populations, with a lower degree of polymorphism. However, the presence of Africanized honeybees in high altitudes and low temperatures observed in Colombia indicate that the restrictions for the colonization of temperate regions by the Africanized swarms are not only due to the temperature. Concerning to the low frequencies of the European patterns in the Africanized populations, the contribution of genes characteristics of subspecies from the M lineage (A. m. iberiensis) is higher, with a very low proportion of C lineage genes (A. m. ligustica). Results of population structure indicate that the Africanized populations are genetically low differentiated. Even though a low fraction of European genes exists in the Africanized populations, we can affirm that the genetic constitution of the honeybees of Americas is a straight result of the introduction of A. m. scutellata in Brazil.
Keywords: Genética de populações; Abelhas africanizadas; Microssatélites; Estrutura populacional; CIENCIAS BIOLOGICAS::GENETICA